2012
DOI: 10.1002/cne.23088
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term interaction between microglial cells and cochlear nucleus neurons after bilateral cochlear ablation

Abstract: The removal of afferent activity has been reported to modify neuronal activity in the cochlear nucleus of adult rats. After cell damage, microglial cells are rapidly activated, initiating a series of cellular responses that influences neuronal function and survival. To investigate how this glial response occurs and how it might influence injured neurons, bilateral cochlear ablations were performed on adult rats to examine the short-term (16 and 24 hours and 4 and 7 days) and long-term (15, 30, and 100 days) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 95 publications
9
51
0
Order By: Relevance
“…An increase in astrocytes was found in chick brainstem after CR in n. magnocellularis , the avian homolog of the anteroventral cochlear nucleus (Rubel and MacDonald, 1992, Lurie and Rubel, 1994). Prior studies in mammals have also shown that both microglia and astrocytes are upregulated in the cochlear nucleus in response to unilateral inner ear lesions in adult rats (de Waele et al, 1996, Campos Torres et al, 1999, Campos-Torres et al, 2005, Fuentes-Santamaria et al, 2012). These studies showed changes in the cochlear nucleus, the primary target denervated by CR.…”
Section: Discussionmentioning
confidence: 87%
“…An increase in astrocytes was found in chick brainstem after CR in n. magnocellularis , the avian homolog of the anteroventral cochlear nucleus (Rubel and MacDonald, 1992, Lurie and Rubel, 1994). Prior studies in mammals have also shown that both microglia and astrocytes are upregulated in the cochlear nucleus in response to unilateral inner ear lesions in adult rats (de Waele et al, 1996, Campos Torres et al, 1999, Campos-Torres et al, 2005, Fuentes-Santamaria et al, 2012). These studies showed changes in the cochlear nucleus, the primary target denervated by CR.…”
Section: Discussionmentioning
confidence: 87%
“…Janz and Illing (2014) found activated microglia in cochlear nuclei as early as one day after cochlear ablation. Fuentes-Santamaria et al (2012) found changes in the relative positions of activated microglia and neurons at 100 days postablation and suggested that the function of these activated microglia was to facilitate changes in neuronal function. Thus the time courses of changes in the cochlea and auditory brainstem following cochlear ablation and noise trauma are very different, and may be mediated by different mechanisms (as suggested by Morest et al, 1998); activated microglia may have different roles in the two paradigms.…”
Section: Discussionmentioning
confidence: 98%
“…The suggestion that activated microglia might participate in auditory plasticity came from studies of a different model of auditory plasticity, cochlear ablation (Campos Torres et al, 1999, Fuentes-Santamaria et al, 2012, Janz and Illing, 2014). Both auditory nerve degeneration and brainstem plasticity occur much more rapidly after cochlear ablations than after acoustic trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the cochlear nucleus regions, glutamine and taurine levels increased in most lesioned-side vestibular nuclear regions as compared to contralateral. Since these two amino acids tend to be more concentrated in glia than in neurons (Patel and Hunt, 1985; Ottersen et al, 1992; Hassel et al, 1995), their increases may be related to the gliosis reported in both cochlear and vestibular nuclei after inner ear lesions (Campos Torres et al, 1999; Li et al, 1999; Fuentes-Santamaría et al, 2012). On the other hand, the increases in glutamine and taurine levels after the peripheral lesion were generally less striking in vestibular nuclei than in the cochlear nucleus, as were any changes in the levels of the other amino acids less closely related to synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%